Observer-based chaos synchronization for secure communications - Sun, Shuwen (My University, 2006)
Chaos, with reference to chaos theory, refers to an apparent lack of order in a system that, nevertheless, obeys particular laws or rules. The chaotic signals generated by chaotic systems have some properties such as randomness, complexity and sensitive dependence on initial conditions, which make them particularly suitable for secure communications. Since the 1990s, the problem of secure communication, based on chaos synchronization, has been thoroughly investigated and many methods, for instance, robust and adaptive control approaches, have been proposed to realize the chaos synchronization. However, from systems theory perspective, it may seem obvious that many robust and adaptive control methods could be considered for possible attacks against secure communication. In this thesis, we introduce the concept of secure chaos synchronization from the control theoretic view point. A new secure communication system, based on the chaos synchronization, is proposed and its security is analyzed, both theoretically and numerically.
Keywords: Chaotic behavior in systems; Computer networks (Security measures); Data encryption (Computer science)